2001
DOI: 10.1038/sj.bjp.0703827
|View full text |Cite
|
Sign up to set email alerts
|

Separation of cannabinoid receptor affinity and efficacy in delta‐8‐tetrahydrocannabinol side‐chain analogues

Abstract: 1 The activities of a number of side-chain analogues of delta-8-tetrahydrocannabinol (D 8 -THC) in rat cerebellar membrane preparations were tested. 4 The e cacies of these compounds varied greatly, ranging from the very low e cacy exhibited to acetylenic compounds such as 1'-heptyn-D 8 -THC and 4'-octyn-D 8 -THC to higher e cacy compounds such as 5'-(4-cyanophenoxy)-1',1'-dimethyl-D 8 -THC and 5'-[N-(4-aminosulphonylphenyl)]-1',1' dimethyl-carboxamido D 8 -THC. All agonist activities were antagonized by the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Although the binding affinities of many ligands may in general correlate well with in vivo activities, 38 there is a recognized disparity between the two properties of affinity and efficacy. 39,40 The classical radioligand binding assay cannot reveal if a molecule is an agonist or an antagonist. 41 This knowledge is valuable especially when incorporating novel, pharmacologically uncharacterized structures into a QSAR model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the binding affinities of many ligands may in general correlate well with in vivo activities, 38 there is a recognized disparity between the two properties of affinity and efficacy. 39,40 The classical radioligand binding assay cannot reveal if a molecule is an agonist or an antagonist. 41 This knowledge is valuable especially when incorporating novel, pharmacologically uncharacterized structures into a QSAR model.…”
Section: Introductionmentioning
confidence: 99%
“…The reported CoMFA models are based either on SAR from one structural class of ligands or from two or more classes of ligands. For the latter models, research groups have attempted to derive common pharmacophoric alignments of structurally different cannabinergic ligands, based on the fact that the ligands displace one another in radioligand binding assays. ,, Commonly, CB1 receptor binding affinities or, in some cases, in vivo pharmacological potencies have been used as biological activity data in the 3D-QSAR models. Although the binding affinities of many ligands may in general correlate well with in vivo activities, there is a recognized disparity between the two properties of affinity and efficacy. , The classical radioligand binding assay cannot reveal if a molecule is an agonist or an antagonist . This knowledge is valuable especially when incorporating novel, pharmacologically uncharacterized structures into a QSAR model.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was observed that the presence of a cyano group doesn't affect all pharmacological potency to the same degree. Thus, cyano substituted D 8 -THC analog (O-774, 29) exhibited similar affinity as 19, but substantial enhancement of in vivo potency {SA (12-fold); TF (4-fold); RT (8-fold)} Griffin et al, 2001;Singer et al, 1998). Shortening the side chain of O-774 (29) by one carbon led to 30, which retained both high affinity and high pharmacological potency.…”
Section: Effects Of Side Chain Substituentsmentioning
confidence: 94%
“…In terms of the 2′-alkenes, the Z-isomers of both 2′-heptene (12) (CB1 Ki = 1.55 nM) 239 and 2′-octene (13) (CB1 Ki = 3.19 nM) 236 showed the most promise, with 2′-pentene-5′-hydroxy (14) (CB1 Ki = 125 nM) 239 and 2′-heptene-6′-acetamide (15) (CB1 Ki = 43.4 nM) 239 paling in comparison. The lack of affinity in the hydrophilic derivatives points strongly to the conclusion that this is a relatively exclusively lipophilic pocket of the receptor.…”
Section: Unsaturated C-3 Side Chain Analogsmentioning
confidence: 99%
“…This tolerance is somewhat evident in the case of 1′,1′-dimethyl-6′-hexanenitrile (33) (CB1 Ki = 1.75 nM; CB2 Ki = 1.1 nM) versus 1′,1′-dimethyl-6′-phenyl-7′-heptanenitrile (36) (CB1 Ki = 18.4 nM; CB2 Ki = 5.75 nM) and 1′,1′-dimethyl-N,N-diethylheptanamide (38) (CB1 Ki = 23.9 nM; CB2 Ki = 2.47 nM). 239 In an attempt to exploit the apparent hydrophobic binding pocket that exists along with the C-3 substituent binding pocket a series of C-1′ cyclic compounds were synthesized (Figure 3.6) for testing. 245 This hydrophobic pocket is evidenced by the fact that 1′,1′-dimethyl compounds bind with far greater affinity than their methylene brethren, and further demonstrated by the lack of binding affinity for the 1′-hydroxyl (42 245 This is an example, though, of a means to gain a 5-fold selection for CB1 over CB2 receptor subtypes.…”
Section: C-1′ Modified Compoundsmentioning
confidence: 99%